Analisis Hambatan dalam Proses Pengambilan Keputusan dan Strategi Penanggulangannya - Togatorop, Gracesya; Muspawi, Mohamad; Togatorop, Graceesya (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Decision-making is a core managerial function that determines the direction of organizational policies and actions. This study aims to analyze the inhibiting factors in the decision-making process and formulate comprehensive strategies to overcome them. This study used a literature study method (library research) by searching scientific sources through the Google Scholar database and national journal repositories, selected based on the criteria of relevance, accreditation, and topic suitability. The results of the study indicate that obstacles to decision-making originate from internal factors, including bounded rationality, escalation of commitment, personal bias, time pressure, and uncertainty; as well as external factors, including rigid organizational structures, ineffective communication, inter-stakeholder conflict, and environmental uncertainty. To overcome these obstacles, organizations can implement data-driven information system strengthening, systematic decision models, collaborative participation, cognitive bias awareness training, decentralization of organizational structures, and effective time management. These findings confirm that the quality of decision-making can be significantly improved through an approach that integrates technical and managerial aspects simultaneously.